Energetic and exergetic analyses of modified combined power and ejector refrigeration cycles. (June 2017) - Rostamzadeh, Hadi; Ghaebi, Hadi; Behnam, Farzaneh
Graphical abstract: Highlights: The traditional CPERC is modified based on the power sub-cycle consideration. The constant-pressure mixing ejector model is taken into account inside of the ejector. The proposed cycles are analyzed based upon the first- and second-law of thermodynamics. Sensitivity analysis of some key parameters of the proposed cycles is carried out. Abstract: This paper aims at improving combined power and ejector refrigeration cycles (CPERCs) performance for low-temperature heat sources. Three modified CPERCs are introduced to improve the basic CPERC (BCPERC) performance based upon the first and second laws of thermodynamics. The proposed cycles consist of two condensers and a separator which have made them different from the traditional combined power and ejector refrigeration cycles. The ejector is driven by the exhaust of the turbine to produce more power and refrigeration, simultaneously. With respect to each proposed cycle, energetic and exergetic analyses have been conducted to understand cycles performance more comprehensively. Throughout these state-of-art modifications, refrigeration and net produced power of cycles are increased, successively. The thermal efficiency, exergetic efficiency, and overall exergy destruction rate of the BCPERC are improved by 8.6 and 24.4, and 16.46%, respectively. Moreover, exergetic analysis demonstrated that among all components, generator has the main contribution in exergy losses for all different CPERCs. At the end, parametric study of some key thermodynamic parameters for different cycles have been conducted to illustrate the variation of key parameters for each cycle. It has been demonstrated that one can obtain a higher thermal efficiency by increasing of the generator and evaporator temperatures or decreasing of the condenser 1 saturated temperature. In addition, a higher exergy efficiency can be obtained by increasing of the generator and evaporator temperatures as well as condenser 1 saturated temperature.